Effectiveness of Cooperative Learning Model and Direct Instruction for Student Learning Achievement - Alhaq, Mutia; Nugraha, Muhamad Arif; Oding, Oding (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2022)
Based on the problems that occur where there are still many students who have not completed their learning achievements, they try to apply a model like this, the study aims to determine the extent to which the effectiveness of cooperative learning and direct instruction learning models can can be used to teach the practice of worship in the management of corpses. The research method used in this study was a quasi-experimental design with a pretest-postest control group design and a quantitative approach. Where the population of this research is all 8th grade students of Mts Darul Falah PPI 61 Cisurupan. The data obtained is the result of the instrument in the form of test questions for the pretest and posttest, and documentation of research results. The instrument analysis includes data validity, reliability, level of difficulty, discriminatory power, normality test, T test, and man whitney test. The result of this research is that when doing a pretest to students the result is that there is no difference in learning achievement between the experimental class and the control class. Furthermore, after a trial was conducted between the experimental class using the cooperative learning model and the control class using direct instruction, the two classes experienced differences in learning achievement, namely the experimental class having further improved student learning outcomes.Berdasarkan permasalahan yang terjadi dimana siswa masih banyak yang belum tuntas pretasi belajar nya sehingga mencoba penerapan model seperti ini,penelitian ini bertujuan untuk mengetahui sejauh mana efektifitas model pembelajaran cooperative learning dan direct instruction dalam pembelajaran praktek ibadah materi pengurusan jenazah, Metode penelitian yang digunakan dalam penelitian ini adalah quasi eksperimen dengan desain prettest-posttest control group design dan dengan pendekatan kuantitatif. Dimana populasi penelitian ini adalah seluruh siswa kelas 8 Mts Darul Falah PPI 61 Cisurupan. Data yang didapat merupakan hasil dari instrument berupa soal tes untuk pretest dan post test, dan dokumentasi hasil penelitian. Untuk analisis instrumen meliputi uji validitas data, reliabilitas, tingkat kesukaran, daya pembeda, uji normalitas, uji T, dan uji man whitney. Hasil dari penelitian ini adalah ketika melakukan pretest kepada siswa hasilnya adalah tidak terdapat perbedaan prestasi belajar antara kelas eksperimen dan kelas kontrol. Selanjutnya setelah dilakukan uji coba antara kelas eksperimen yang menggunakan model cooperative learning dan kelas kontrol menggunakan direct instruction, kedua kelas tersebut mengalami perbedaan prestasi belajar, yaitu kelas eksperimen lebih meningkatkan hasil prestasi belajar siswa.